## ∫sinx dx =

### -cosx + C

∫sin(x) dx = -cos(x) + C

where C is the constant of integration. This is because the derivative of -cos(x) is sin(x) by the chain rule of differentiation.

Alternatively, we can use integration by substitution. Let u = x, then du/dx = 1 and dx = du. Substituting these into the original integral:

∫sin(x) dx = ∫sin(u) du

Using the fact that sin(u) is the derivative of -cos(u), we have:

∫sin(x) dx = -cos(u) + C

Substituting back u = x, we get:

∫sin(x) dx = -cos(x) + C

##### More Answers:

How To Integrate Sec(X)Tan(X) Using U-SubstitutionStep-By-Step Guide: Finding The Antiderivative Of Csc^2X Using U-Substitution And The Power Rule Of Integration

Master The Integration Of Sec²X With Substitution Method: Antiderivative Of Sec²X Simplified

Error 403 The request cannot be completed because you have exceeded your quota. : quotaExceeded